Peningkatan Efisiensi Proses Operasional Lelang Melalui Pembuatan Learning Management System (LMS) Berbasis Google Sites pada KPKNL Surakarta - Novi Alviana; Zahrotul Mufidah; Lathifa Rahma Zuhaida; Sudiyanto Sudiyanto (Jurnal Kabar Masyarakat, 2023)
Nowadays, technology is a very significant phenomenon that has an impact on the digitization of knowledge. One example of technological development is the digitization of information through the Learning Management System (LMS) website. Due to its limited features, the Learning Management System (LMS) website was not very popular at first. But nowadays, Learning Management System (LMS) websites are available online and used as a source of learning content. Information integrated with the Learning Management System (LMS) site-based information system offers an easy and convenient interface service used for various activities such as information accuracy. In this era, Learning Management System (LMS) sites are considered important for both government and private segments, because the Learning Management System (LMS) provides information to the public without distance and time limitations. KPKNL Surakarta is a government institution located in Banjarsari District. One of the services provided is auction. In the course of auction activities, this institution faces challenges, such as the lack of easy access for the public to obtain information on auction procedures. This research aims to develop a Learning Management System (LMS) site based on google sites in a systematic and structured manner. This research consists of situation analysis, problem identification, goal setting and planning, problem solving plan, implementation and planning.